Sosialisasi Potensi Mangrove sebagai Bahan Baku Produk Olahan Lokal: Upaya Awal Pemberdayaan Masyarakat Pesisir Bojong Salawe Pangandaran - Wijayanti, Lady Ayu Sri; Maziyya, Nur; Febrianto, Firman; Alamsyah, Muhammad; Hasan, Zidane Al Fikri (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The mangrove ecosystem in the coastal area of ​​Bojongsalawe, Pangandaran Regency, holds potential as a source of local food products. However, community knowledge regarding usable mangrove species, nutritional content, processing techniques, and product development opportunities remains limited. This community service activity aimed to enhance coastal community knowledge concerning the potential use of mangroves as raw materials for local processed products. Nineteen participants took part in the activity, which employed a participatory educational approach comprising a pre-test, presentations on ecological and economic aspects, interactive discussions, sensory evaluation and product tasting, and a post-test. The products introduced included mangrove leaf sticks and dodol (a traditional confection) made from bogem fruit (Sonneratia caseolaris), alongside information on the potential use of nipa palm sap (Nypa fruticans). Evaluation results showed that the participants' average knowledge score rose from 52.6 in the pre-test to 84.2 in the post-test (Δ = 31.6). These results indicate that the outreach activity successfully increased participants' understanding of the ecological functions of mangroves and opportunities for their utilization as local food sources. Follow-up activities such as production training, product standardization, and business mentoring are required to translate this increased knowledge into practical skills and sustainable economic activities.